(untitled) (Zien Journal of Social Sciences and Humanities, 2024)
The article discusses the daily life of the population during the Mangid rule, based on historical works, travelogues and other sources created in the first half of the 18th-19th centuries. In particular, it emphasizes the importance of streets, alleys, neighborhoods, their role in various residential areas, parks, recreation areas, housing, clothing, food culture, leisure activities, and various ceremonies, which played an important role in the daily life of the population. The information presented in the article serves as additional material to the works published internationally so far